Evaluation Of Cardioprotective Efficacy Of Nelumbo Nucifera Leaf Extract On Isoproterenol-Induced Myocardial Infarction In Wistar Rats - R. SUBASHINI,; M. RAJADURAI, (International Journal of Pharma and Bio Sciences, 2011)
Intake of diets rich in antioxidant from medicinal plants have been reported to be associated with reduced risk of cardiovascular diseases. The present study was aimed to appraise the protective role of Nelumbo nucifera leaf extract in isoproterenol-induced myocardial infarction in rats. Subcutaneous injection of isoproterenol (85 mg/kg) to male albino Wistar rats, exhibited a significant raise in the levels/activities of cardiac marker such as cardiac troponin T, creatine kinase-MB, creatine kinase, lactate dehydrogenase, asparate transaminase, alanine transaminase in serum with subsequent decrease in the heart. Isoproterenol-induced rats also showed a significant increase in the levels of blood glucose, serum urea, uric acid, creatinine and homocysteine and decrease in plasma protein. Pretreatment with Nelumbo nucifera (100, 200 and 400 mg/kg) daily for a period of 21 days positively altered the activities of cardiac markers and other biochemical parameters to isoproterenol-induced rats. Thus, the results of our study demonstrate that Nelumbo nucifera possess cardioprotective role against experimentally induced cardiac toxicity.